2020
DOI: 10.3390/ijerph17145086
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Floating Catchment Area Model-Based Evaluation of Community Care Facilities’ Spatial Accessibility in Xi’an, China

Abstract: Due to the rapid increase in the number of elderly people in Chinese cities, the development and planning of aged care facilities, and particularly community care facilities, which will gradually become the mainstream choice for the elderly in China, is becoming an important topic for urban sustainability. Previous studies have shown that the number and scale of aged care facilities in many cities are far from meeting the needs of the elderly and the overall occupation rate is low. Some of these cities are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Among different aspects of AFCC, age-friendly facilities are proved to be an essential factor related to SUD. Liu et al [41] stressed that providing enough community-based care facilities has been the main task for Xi'an's SUD. Zaman and Thornton found that building an age-friendly environment and facilities can facilitate Unley's SUD goal by fulfilling citizens' dignity and equality in a healthy environment [42].…”
Section: Age-friendly and Sustainable Development-an Integration Perspectivementioning
confidence: 99%
“…Among different aspects of AFCC, age-friendly facilities are proved to be an essential factor related to SUD. Liu et al [41] stressed that providing enough community-based care facilities has been the main task for Xi'an's SUD. Zaman and Thornton found that building an age-friendly environment and facilities can facilitate Unley's SUD goal by fulfilling citizens' dignity and equality in a healthy environment [42].…”
Section: Age-friendly and Sustainable Development-an Integration Perspectivementioning
confidence: 99%
“…First, this study compensates for the limitations of previous studies, some of which took only spatial factors into consideration [40,47,57,58] or positioned population demand at the geometrically weighted center points of the population [18,47,48]. The limitations of exact locations of the population demand were addressed by using BSA data to solve problems of MAUP.…”
Section: Discussionmentioning
confidence: 99%
“…Tao et al [40] sought to optimize the allocation of elder care facilities, using the current spatial distribution of the elderly population in Beijing, China, and a model developed to ensure maximum equity. Liu et al [48] integrated a two-step floating catchment area (2SFCA) method and a potential model to assess a better search radius. This study demonstrated that 600 m is close to the real travel distance of the elderly in Xi'an, China.…”
Section: Optimization Of Community-based Care Resourcesmentioning
confidence: 99%
“…Through the above research, in order to improve the spatial balance of accessibility in Shaanxi and provide reference for the development of public health in other inland areas of the world, the following are suggested: (1) To solve the problem of insufficient medical resources, the government should promote investment, attract or encourage through policy more medical institutions and talents to flow into inland areas, and expand medical servicecapacity, improving the level of accessibility to medical services, so as to alleviate the competition pressure of medical resources. (2) In order to solve the problem of polarization of medical-service accessibility and high cost of medical treatment for residents in remote areas, it is necessary to increase the construction of basic transportation networks, especially the road networks in mountainous and hilly areas like Shaannan and Shaanbei, and transfer financial investment from the construction of high-level and large-scale road networks to the improvement of low-level and small-scale road networks. The government should promote the trickle-down effect of central cities, guide the inflow of some medical resources to the underdeveloped areas, and evacuate agglomeration centers to achieve a balance among regions.…”
Section: Policy Suggestionmentioning
confidence: 99%
“…At present, the actual medical behavior of Chinese residents is mainly affected by the different medical needs caused by disease types. Therefore, the accurate and reasonable evaluation of the current state of medical services on the basis of actual medical needs of residents to guide policy formulation in order to promote the rational and equitable distribution of medical facilities and maximize social benefits is in line with people’s wishes, which is an important means to maintain economic development and social stability [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%